Rodent proliferation in urban and agricultural settings of sub-Saharan Africa. The dark side of synthetic chemical rodenticides - (:unkn) unknown (My University, 2023)
Around 400 million people in the world are affected by zoonoses associated with rodents. In addition, at least 280 million cases of undernourishment could be avoided in the world by the effective management of populations of rodents which destroy crops and stores of crops. Consequently, managing rodent populations which are reservoirs of pathogenic agents or which destroy crops and stores of crops is a challenge both in terms of food security as well as public health. In terms of public policy, many African countries have established farming intensification programmes aiming to improve their food self-sufficiency, with the direct risk of the prolifera-tion of rodents. In this article, which is the first in a two-part series, we present the background to controlling rodents in Africa in rural and urban areas, followed by an overview of the regu-lations and uses of rodenticides. We will go on to document the problematic situations which result from this, illustrating them with case studies. The use of synthetic chemical rodenticidesis the most widely used method to control rodents and is not only toxic for humans, other animals and the environment, but also ineffective against rodent populations (for example, it is costly, leads to a build-up of resistance, and the avoidance of bait). The circulation and uncontrolled use of these rodenticides in many African countries is associated with conside-rable risks to health and the environment, without leading to any significant improvements in terms of rodent control or reducing the damage they cause.
Keywords: African Research